2010
DOI: 10.4236/jbpc.2010.11006
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between delayed fluorescence of chlorophyll, metabolism and yield of plants. II. Influence of moisture of leaf and temperature condition on delayed fluorescence of leaves

Abstract: During various temperatures of incubation the dehydration of leaves up to 3.2-3.8% mainly induced increase maximum amplitude of delayed fluorescence of chlorophyll. It was shown that moisture loss with this range could be determined for the most part by the growth of the electrochemical potential of thylakoid membranes. The further incubation of detached leaves at 36℃ temperature, with more notable moisture loss, resulted in specific its decline as opposed to cases of 22 and 6℃ of thermal incubation. It was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The decay of induction curve was generally explained by a decrease in the membrane energization as a result of secondary cation efflux from thylakoids [11,12]. Our results showed that half time of I decay-τ describe the level of interaction LR and DR of plants [13,14].This is a biological base triggering the use of these DF parameters in physiological research. The interest of using the parameters of this luminescence for the diagnosis of plants' state is identified also by the possibility of their fast measurements on intact objects by the use of comparatively simple and accessible equipment.…”
Section: Introductionsupporting
confidence: 53%
See 4 more Smart Citations
“…The decay of induction curve was generally explained by a decrease in the membrane energization as a result of secondary cation efflux from thylakoids [11,12]. Our results showed that half time of I decay-τ describe the level of interaction LR and DR of plants [13,14].This is a biological base triggering the use of these DF parameters in physiological research. The interest of using the parameters of this luminescence for the diagnosis of plants' state is identified also by the possibility of their fast measurements on intact objects by the use of comparatively simple and accessible equipment.…”
Section: Introductionsupporting
confidence: 53%
“…Under continuous influence of virus infection, changes in the DF parameters were observed analogously, caused by water stress on potato, modified by doses of phosphorus fertilizers [13], leaf prolonged dehydration and frosts influence [14], which also being correlated with the changes of yield. Therefore, these results allow recommend the use of DF parameters in the systems analysis of production process.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations